Hubungan hipertensi dengan kejadian stroke di RSUD Kotamobagu - Saharman, Salni; Winarto, Eko (Universitas Wiralodra, 2023)
Stroke is the second leading cause of death and the third leading cause of disability in the world. Stroke according to the World Health Organization (WHO) is a condition in which clinical signs develop rapidly in the form of focal and global neurologic deficits that can be severe and last for 24 hours or more and or can cause death, without any other obvious cause other than vascular. This study aims to determine the relationship between Hypertension and stroke event in the inpatient room at RSUD Kotamobagu. Method of Research on This study used a descriptive analytic research design using a cross sectional approach. The number of samples in this study were 137 respondents. The sampling technique is by systemati random sampling. Research Results : This is evidenced by the statistical test p = 0.001 < = 0.05) the correlation coefficient (r) = 1.000 indicates a very strong relationship. It is proven that patients who suffer from hypertension have a great risk of suffering from stroke. Conclusions and Suggestions Based on the results of research on the relationship between hypertension and stroke events at RSUD Kotamobagu which was conducted on 137 respondents, the results obtained were: The highest proportion of hypertension was 93.43%, the highest proportion of stroke was 93.43%. There is a relationship between hypertension and the incidence of stroke in RSUD Kotamobagu. Suggestions for the Hospital to be able to publish to the wider community the impact caused by hypertension if it is not handled properly and quickly because it can cause a stroke.